Paper Sector in Bangladesh: Challenges and Scope of Development (Journal of Chemical Engineering, 2012)
Pulp and paper sector in Bangladesh is used to get less importance in comparison with that of other sectors related to socioeconomic development of the country. KPML, the oldest integrated pulp and paper industry in Bangladesh built in the early fifties of last century is still in operation. Recently, almost hundred paper mills are erected and most of those are in operation and producing varieties of papers. This article deals with the problems in operating the mills and makes suggestions to improve its operation and productivity. The major challenges in paper sector and the scope of development is discussed. DOI: http://dx.doi.org/10.3329/jce.v26i1.10181 JCE 2011; 26(1): 41-46